Filsafat Dan Sains Prespektif Yunani Dan Islam - Ramadhana, Muhammad Nasrullah; Amin, Mat; OK, Azizah Hanum (Universitas Pahlawan Tuanku Tambusai, 2024)
Aqidah This research aims to explain the development of philosophy and science in ancient Greece and the Islamic era. The type of research used in this study is a literary study using a descriptive analytical approach method. This research was carried out by collecting various kinds of information and studying various literature related to the Development of Philosophy in Science, Palda Zamaln Yulnani and the Islamic Era. The results of this research show that Philosophy and Science in the Yulnan Era was a very important period due to the emergence of the human thought pattern from mythocentric to logocentric. And during the golden age of Islamic civilization (750-1258 AD), Muslim scholars developed philosophy and science by adopting and modifying Greek thought. Keywords: Philosophy, Science, Greece, Islamic